Constraints to adopting soil fertility management practices in Malawi: A choice experiment approach. (December 2019) - Krah, Kwabena; Michelson, Hope; Perge, Emilie; Jindal, Rohit
Highlights: We analyze constraints to the adoption of soil fertility management (SFM) practices. We examine the design of policy options to induce adoption of SFM practices. We show that farmer liquidity and technical knowledge limitations impede adoption. Farmer perception of climate variability correlates with preferences for SFM practices. Abstract: Though problems related to low and declining soil fertility continue to impede agricultural production and food security in Sub-Saharan Africa, smallholder farmers in this region – those cultivating two hectares or less – have shown reluctance to adopt practices at scale that help conserve or enhance soil quality. Employing a discrete choice-based experiment, we find evidence that farmers' propensity to adopt soil fertility management (SFM) practices increases with improved access to mineral fertilizers, and when farmers receive relevant technical training on soil fertility improving technologies. A unique aspect of our study is our focus on understanding how smallholders' stated SFM preferences relate to their perceptions of recent local climatic variation. We find that farmers who perceive that rainfall amounts are decreasing are less willing to adopt crop rotations to improve soils. Our findings suggest that policies designed to increase adoption of SFM practices are more likely to succeed when they provide farmers with inputs that farmers perceive as complementary to SFM, including mineral fertilizer, and when they are built around an understanding of farmers' perceptions of climatic variability.